2019
DOI: 10.1038/s41467-019-09215-9
|View full text |Cite|
|
Sign up to set email alerts
|

Unusual substrate and halide versatility of phenolic halogenase PltM

Abstract: Controlled halogenation of chemically versatile substrates is difficult to achieve. Here we describe a unique flavin-dependent halogenase, PltM, which is capable of utilizing a wide range of halides for installation on a diverse array of phenolic compounds, including FDA-approved drugs and natural products, such as terbutaline, fenoterol, resveratrol, and catechin. Crystal structures of PltM in complex with phloroglucinol and FAD in different states yield insight into substrate recognition and the FAD recyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…This can be explained as in both structures the FAD-binding loop is part of a crystal contact, with the loops of two chains interacting with each other, generating a noncrystallographic twofold axis. In PltM, the conformation is very similar to that observed for 'closed' loop conformations (Mori et al, 2019). This is in contrast to the 'open' loop position in RebH (Bitto et al, 2008), where the loop is not in direct contact with the cofactor, leaving the FAD-binding site solvent exposed.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This can be explained as in both structures the FAD-binding loop is part of a crystal contact, with the loops of two chains interacting with each other, generating a noncrystallographic twofold axis. In PltM, the conformation is very similar to that observed for 'closed' loop conformations (Mori et al, 2019). This is in contrast to the 'open' loop position in RebH (Bitto et al, 2008), where the loop is not in direct contact with the cofactor, leaving the FAD-binding site solvent exposed.…”
Section: Discussionsupporting
confidence: 51%
“…The first FDHs to be characterized were tryptophan halogenases (Trp halogenases; Keller et al, 2000;Yeh et al, 2005). In the following years, a variety of different halogenases were studied that can be grouped into indole halogenases (which include the Trp halogenases; Seibold et al, 2006;Heemstra & Walsh, 2008;Zeng & Zhan, 2011;Menon et al, 2016;Ma et al, 2017;Lingkon & Bellizzi, 2020;Domergue et al, 2019;Luhavaya et al, 2019), phenol halogenases (Buedenbender et al, 2009;Neumann et al, 2010;Zeng et al, 2013;Agarwal et al, 2014;Menon et al, 2017;Mori et al, 2019) and pyrrole halogenases (Hammer et al, 1997;Dorrestein et al, 2005;Yamanaka et al, 2012;Agarwal et al, 2014), depending on the classes of compounds that they halogenate.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain anion preferences exist: The well described Trp-Fl-Hals RebH, Thal and PyrH prefer chlorination over bromination [24,25,27], while BrvH and VirX1 prefer bromination over chlorination [22,35]. For the three xcc-b100 enzymes, no chlorination was observed, and iodination was only found for Bmp5, PltM, and VirX1 [34,35,40,45] ( Table 1).…”
Section: Enzyme Diversity and Substrate Scopementioning
confidence: 99%
“…The authors found that PltM can halogenate several small phenolic and aniline derivatives. Encouraged by these findings, the study was successfully continued towards more bulky compounds including FDA approved drugs and natural products such as terbutaline, fenoterol, resveratrol, and catechin ( Figure 10) [45]. Notably, no halogenation activity was observed in the case of a nitrobenzene derivative due to the strongly electron withdrawing nitro group that prevented the halogenation of the substrate.…”
Section: Substrate Scope and Regioselectivitymentioning
confidence: 99%
See 1 more Smart Citation